Pengaruh Likuiditas Saham Dan Capital Structure Terhadap Return Saham (Universitas Gresik, 2023)
The purpose of this study is to test and analyze the effect of stock liquidity and capital structure on stock returns in manufacturing companies listed on the Indonesia Stock Exchange. Companies with capital structures that are dominated by debt tend to be shunned by investors, because high debt is a burden they will bear when they become shareholders. Companies with a capital structure dominated by debt certainly provide smaller returns to shareholders due to the large cost of interest and debt so that the use of debt in the company gives a negative signal to investors. This study uses a quantitative research approach where researchers measure variables, test hypotheses, and draw conclusions from findings so that they can be generalized. Furthermore, it was concluded that stock liquidity has a significant positive effect on stock returns. This shows that the greater the liquidity of the company's shares, the higher the return on shares in the company. Capital structure has a significant negative effect on stock returns, this shows that the greater the capital structure in the company, the smaller the stock return obtained by the company. Company size (SIZE) does not have a significant effect on stock returns. This shows that the size of the company (SIZE) does not affect the return of shares in the company. The age of the company (AGE) does not have a significant effect on stock returns. This shows that the age of the company (AGE) does not affect the return on shares in the company. Growth Opportunity has a significant positive effect on stock returns, it shows that the greater the company's growth opportunity, the higher the stock return on the company